The Economics of Skyscrapers: A Synthesis - Gabriel Ahlfeldt; Jason Barr (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper provides a synthesis of the state of knowledge on the economics of skyscrapers. First, we document how vertical urban growth has gained pace over the course of the 20th century. Second, we lay out a simple theoretical model of optimal building heights in a competitive market to rationalize this trend. Third, we provide estimates of a range of parameters that shape the urban height profile along with a summary of the related theoretical and empirical literature. Fourth, we discuss factors outside the competitive market framework that explain the rich variation in building height over short distances, such as durability of the structures, height competition, and building regulations. Fifth, we suggest priority areas for future research into the vertical dimension of cities.
Keywords: R30; N90; 330; density; economics; history; skyscraper; urban